PaySwitch: Smart Contract-Based Payment Switch for Off-Chain Payment Channel Networks - Anan Jin; Yuhang Ye; Brian Lee; Xiang Li; Yuansong Qiao (IEEE Access)
Payment channel networks (PCNs) are a viable solution to the issue of blockchain scalability by offering off-chain transactions between two untrusted peers, without committing each transaction to the blockchain. The payment channel cannot be used when its deposit is depleted, which hinders the payment completion, such as it is overly utilized in one direction. However, they cannot migrate the deposit from one channel to another to facilitate payment completion when a depletion in the channel deposit arises. This limitation arises from the basic design assumption of payment channels, i.e., each channel is independent from others. To overcome this limitation, this paper proposes PaySwitch, inspired by the traditional network switch, to enable connecting multiple payment channels through one PaySwitch smart contract. PaySwitch is designed to enable any peer in the PaySwitch to dynamically reallocate the deposits in their payment channels while maintaining the independence of each other to ensure the trustworthiness of the channel. This paper presents the security definition of PaySwitch and formally proves its security using the UC-framework. To demonstrate the feasibility of PaySwitch, this paper applies it to several routing algorithms. The experimental results show that PaySwitch is capable of improving the transaction success rate and throughput compared with the traditional payment channel based approaches.